2021
DOI: 10.1108/ejim-01-2021-0045
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between subjective well-being, perceived organisational culture and individual propension to innovation

Abstract: PurposeThis paper analyses the relationship between subjective well-being (SWB) and perceived organisational culture (POC) with the individual propensity to innovation (IPI).Design/methodology/approachTo empirically test the hypotheses, the sample and data were collected through a cross-sectional survey with 614 professionals who work in Technological Knowledge-Intensive Business Service (T-Kibs) in Brazil. For data analysis, the authors applied the partial least squares path modelling (PLS-PM) algorithm.Findi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 97 publications
0
8
2
1
Order By: Relevance
“…Cameron et al [35] explain that the adhocracy culture supports the generation of new ideas, innovation and creativity. However, in a study in Brazil conducted in the T-Kibs organisations, it was found that the market culture supports innovation, whereas the clan, adhocracy and hierarchical organisational cultures did not have an influence on innovation in this study [5]. Further research confirmed that the clan and rational culture have a positive influence on creativity; however, it was also established that the influence of the clan culture on creativity did not appear to be affected as a result of whether computer-mediated communication or face-to-face communication was used.…”
Section: Creativity and Innovation In An Organisational Culture Contextcontrasting
confidence: 81%
See 3 more Smart Citations
“…Cameron et al [35] explain that the adhocracy culture supports the generation of new ideas, innovation and creativity. However, in a study in Brazil conducted in the T-Kibs organisations, it was found that the market culture supports innovation, whereas the clan, adhocracy and hierarchical organisational cultures did not have an influence on innovation in this study [5]. Further research confirmed that the clan and rational culture have a positive influence on creativity; however, it was also established that the influence of the clan culture on creativity did not appear to be affected as a result of whether computer-mediated communication or face-to-face communication was used.…”
Section: Creativity and Innovation In An Organisational Culture Contextcontrasting
confidence: 81%
“…Creativity is critical for organisational success [1], while innovation is regarded as a driver for organisational growth, resilience [2], sustainability [3], performance [4] and competitiveness [5]. Creativity and innovation are becoming a core part of organisational strategies to achieve success and to incorporate technology changes [6], these being key factors that can aid organisations to adapt in a world where there is an accelerated pace of change [7].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Creativity is critical to organisational success (Andleeb et al , 2020), while innovation is regarded as a driver for organisational growth, resilience (Javanmardi et al, 2021), sustainability (Robbins et al , 2018), performance (Strychalska-Rudzewicz and Rudzewicz, 2021) and competitiveness (Bianchi et al , 2021). Creativity and innovation are becoming a core part of organisational strategies to achieve success and to incorporate technology changes (Shahzad et al , 2017); these being key factors that can aid organisations to adapt in a world where there is an accelerated pace of change (Martins and Terblanche, 2003).…”
Section: Introductionmentioning
confidence: 99%